Factors associated with malnutrition risk among elderly with chronic obstructive pulmonary disease from Hospital Serdang and Institut Perubatan Respiratori - Y., Nor Farahin; O., Noraida; N., Muhammad Zaki; D., Ummi Nadira; M. Y., Barakatun Nisak; A., Siti Nur'Asyura (Community Health Society Malaysia, 2019)
Background: Malnutrition is present in both Chronic Obstructive Pulmonary Disease (COPD) and elderly patients. The occurrence of malnutrition in the elderly together with COPD could lead to mortality. Therefore, this study was conducted to determine factors that are associated with malnutrition risk among the elderly with COPD.